Changes in Leaf-Level Nitrogen Partitioning and Mesophyll Conductance Deliver Increased Photosynthesis for Lolium perenne Leaves Engineered to Accumulate Lipid Carbon Sinks - Cooney, Luke J.; Beechey-Gradwell, Zac; Winichayakul, Somrutai; Richardson, Kim A.; Crowther, Tracey; Anderson, Philip; Scott, Richard W.; Bryan, Gregory; Roberts, Nicholas J. (Frontiers in Plant Science, 2021)
Diacylglycerol acyl-transferase (DGAT) and cysteine oleosin (CO) expression confers a novel carbon sink (of encapsulated lipid droplets) in leaves of Lolium perenne and has been shown to increase photosynthesis and biomass. However, the physiological mechanism by which DGAT+CO increases photosynthesis remains unresolved. To evaluate the relationship between sink strength and photosynthesis, we examined fatty acids (FA), water soluble carbohydrates (WSC), gas exchange parameters and leaf nitrogen for multiple DGAT+CO lines varying in transgene accumulation. To identify the physiological traits which deliver increased photosynthesis, we assessed two important determinants of photosynthetic efficiency, CO2 conductance from atmosphere to chloroplast, and nitrogen partitioning between different photosynthetic and non-photosynthetic pools. We found that DGAT+CO accumulation increased FA at the expense of WSC in leaves of Lolium perenne and for those lines with a significant reduction in WSC, we also observed an increase in photosynthesis and photosynthetic nitrogen use efficiency. DGAT+CO Lolium perenne displayed no change in rubisco content or Vcmax but did exhibit a significant increase in specific leaf area (SLA), stomatal and mesophyll conductance, and leaf nitrogen allocated to photosynthetic electron transport. Collectively, we showed that increased carbon demand via DGAT+CO lipid sink accumulation can induce leaf-level changes in Lolium perenne which deliver increased rates of photosynthesis and growth. Carbon sinks engineered within photosynthetic cells provide a promising new strategy for increasing photosynthesis and crop productivity.